Efektivitas Bokashi, Trichoberas, dan PGPR Terhadap Penyakit Antraknosa Pada Tanaman Cabai Rawit - Syafira, Faulyna; Mariana, Mariana; Budi, Ismed Setya (JURNAL PROTEKSI TANAMAN TROPIKA, 2024)
The use of biological agents is an alternative to control anthracnose disease caused by the pathogen Colletotrichum sp. on chilies. This research aims to determine the effectiveness of Bokashi, Trichoberas, and PGPR and their combination in reducing the incidence of anthracnose disease and the growth of cayenne pepper plants. This research used the Completely Randomized Design (CRD) method. One factor tested was the type of biological agent and its combination. Carried out in vivo in polybags, Colletotrichum sp. applied when the chili plants start to bear fruit. Observations were made on disease incidence and growth parameters and production of chili plants. The results of the study showed that the application of Bokashi, Trichoberas, and PGPR and their combination significantly reduced the incidence of anthracnose with the lowest percentage of disease incidence in the combination treatment of Bokashi and Trichoberas at 33.61% with control effectiveness of 54.27%; the combination of Bokashi and PGPR was 38.70% with control effectiveness of 47.34% and the combination of Bokashi, PGPR and Trichoberas was 41.07% with control effectiveness of 44.11% and was included in the quite effective category, but had no effect on the incubation period. The PGPR, Bokashi, and Bokashi+ PGPR treatments were able to increase plant height and accelerate the age of first flowering. The Bokashi+Trichoberas, Bokashi+PGPR+Trichoberas and Bokashi+PGPR treatments were able to increase the fresh weight of the fruit.